A metrological atomic force microscope for large range measurements with sub-nanometre resolution - Wu, Yiting; Wirthmann, Elisa; Klöpzig, Ute; Hausotte, Tino (Sensor and Measurement Science International 2021, 2021)

A metrological atomic force microscope system - Wu, Yiting; Wirthmann, Elisa; Klöpzig, Ute; Hausotte, Tino (Nano Express, 2021)
A new metrological atomic force microscope (MAFM) with combined deflection detection system that comprises a homodyne interferometer and an optical beam deflection measuring system are presented. The combination allows the simultaneous three-dimensional detection of position, bending and torsion of the cantilever. Two wedge plates with a wedge angle of 0.5° have been integrated to reduce the disturbing interferences. The new measuring system uses two tiltable plane mirrors and a shiftable focus lens to adjust the direction of the focused laser beam and the position of the focus. The integration of the MAFM head in a nanomeasuring machine (NMM-1) creates the possibility of traceable dimensional measurements over a large range of 25 mm × 25 mm × 5 mm with sub-nanometre resolution. This paper introduces its setup, realisation and metrological properties, such as stability of the characteristic curves, noise level and combined measurement uncertainty. Finally, exemplary measurement results are presente
Keywords: metrological atomic force microscope; combined deflection detection system; reducing disturbing interference; combined measurement uncertainty

Atomic force microscope with an adjustable probe direction and piezoresistive cantilevers operated in tapping-mode - Schaude, Janik; Albrecht, Julius; Klöpzig, Ute; Gröschl, Andreas Christian; Hausotte, Tino (Technisches Messen, 2019)
This article presents a new tilting atomic forcemicroscope (AFM) with an adjustable probe direction and piezoresistive cantilever operated in tapping-mode.The AFM is based on two rotational axes, which enable the adjustment of the probe direction to cover a complete hemisphere. The whole setup is integrated into a nano measuring machine (NMM-1) and the metrological traceability of the piezoresistive cantilever is warranted by in situ calibration on the NMM-1. To demonstrate the capabilities of the tilting AFM, measurements were conducted on a step height standar
Keywords: Atomic force microscopy; tilting AFM; piezoresistive cantilever; nano measuring machine

Development of a Metrological Atomic Force Microscope System with Improved Signal Quality - Wu, Yiting; Wirthmann, Elisa; Klöpzig, Ute; Hausotte, Tino (Engineering Proceedings, 2021)
This article presents a new metrological atomic force microscope (MAFM) with a homodyne interferometer and a tilt measuring system by a position sensitive device (PSD). The combination allows simultaneous three-dimensional detection of the tip displacement by capturing the position, bending and torsion of a reflecting surface of the cantilever realized with one laser beam. Based on an existing interferometric measuring head of a micro-tactile 3D probe, the sensor head was revised and adapted for atomic force microscopy. The new measuring system uses two tiltable plane mirrors to adjust the direction and position of a focused laser beam. With this adjustment unit, the focused laser beam can be steered perpendicular to the reflecting backside of the cantilever. Regarding the probe system, the optical design of the measuring head has been reengineered to reduce the disturbing interference on the PSD. A simulation applying the optical design program OpticStudio from Zemax shows that the integration of two wedge plates with a wedge angle of 0.5° reduces the disturbing interference significantly. After manufacturing, initial measurement results are presented to verify the functionalit
Keywords: metrological atomic force microscope (MAFM); tiltable plane mirrors; reduced disturbing interference

Investigation of a metrological atomic force microscope system with a combined cantilever position, bending and torsion detection system - Wu, Yiting; Wirthmann, Elisa; Klöpzig, Ute; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2021)

Investigation of a metrological atomic force microscope system with a combined cantilever position, bending and torsion detection system - Wu, Yiting; Wirthmann, Elisa; Klöpzig, Ute; Hausotte, Tino (Sensor and Measurement Science International 2020, 2020)
This article presents a new metrological atomic force microscope (MAFM) with adjustable beam posi-tion and direction of the cantilever measuring system. An interferometric measurement system measures the position of the cantilever and a quadrant photodiode detects the bending and torsion of the cantilever. To improve the signal quality and reduce disturbing interferences, the optical design was changed in comparison to the system of [3, 4]. The integration of the MAFM in the nanomeasur-ing machine (NMM-1) offers the possibility of large-scale measurements over a range of 25 mm × 25 mm × 5 mm with subnanometre resolution. A large number of measurements have been performed by this MAFM in combination with the NMM-1. In this short paper, examples of these measurements for determination of step height and pitch and the measurement of an area are demonstrated.<br
Keywords: metrological atomic force microscope; nanomeasuring machine

Large Range Self-Sensing Atomic Force Microscope (LR-SAFM) for Surface Topography - El Melegy, Ahmed; Hausotte, Tino; Mohammed Abu, El-Wahed Younes; Mohammed Ahmed, Amer; Weinert, Benedict; Klöpzig, Ute (IEEE IST 2016 Conference Proceeding, 2016)